The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.

L’offre active et l’accessibilité des services sociaux et de santé chez les personnes atteintes de démence en contexte francophone minoritaire - Bélair, Josée (Université d'Ottawa, 2019)
À l’heure actuelle, les besoins de soins de santé augmentent en réponse à la démographie vieillissante (Organisation mondiale de la santé, 2018). Pourtant, la difficulté d’accès aux services sociaux et de santé chez les usagers en situation minoritaire est une réalité présentée à l’aide de la littérature scientifique. En ce qui a trait aux populations minoritaires de la ville d’Ottawa, les études antérieures permettent de démontrer les obstacles touchant plus particulièrement les personnes francophones dans l’accessibilité des services sociaux et de santé (Kubina et collab., 2018). Dans le contexte de cette étude qualitative, le diagnostic de démence est pris en compte en tant que facteur explicatif de la difficulté accrue vécue chez les aînés francophones dans le recours aux services sociaux et de santé (Carbonneau et Drolet, 2014b). Un total de cinq proches aidants de la ville d’Ottawa a été recruté dans le but d’alimenter les objectifs de la recherche, c’est-à-dire : 1) d’identifier les barrières linguistiques dans la trajectoire des services sociaux et de santé ; 2) d’identifier l’influence des structures du Cadre d’analyse des leviers d’action pour l’accès et l’intégration des services sociaux et de santé pour les communautés de langue officielle en situation minoritaire (CALA) (Savard et collab., 2017) (Voir figure 1) dans l’accès aux services sociaux et de santé chez la population à l’étude. Quoique la majorité des participants à la recherche aient exprimé leur satisfaction par rapport aux services en français reçus pour leur proche atteint d’une démence, certaines barrières linguistiques telles que le manque de continuité dans les services en français ont été identifiées ainsi que le manque d’information quant à la disponibilité des services dans la communauté. De plus, la majorité des participants à la recherche ont pu identifier au moins un moment où les services à leur disponibilité étaient strictement en anglais. Bref, parmi les cinq proches aidants interviewés, quatre ont mentionné la nécessité de lutter pour l’obtention des services en français.

Access to resources in the community through navigation: Protocol for a mixed-methods feasibility study - Dahrouge, Simone; Gauthier, Alain; Chiocchio, François; Presseau, Justin; Kendall, Claire; Lemonde, M.; Chomienne, Marie-Hélène; Perna, A.; Toal-Sullivan, Darene; Devlin, R. A.; Timony, Patrick; Prud'homme, Denis (JMIR Publications, 2019)
Background: Community-based health and social resources can help individuals with complex health and social needs achieve their health goals. However, there is often inadequate access to these resources due to a lack of physician and patient awareness of available resources and the presence of social barriers that limit an individual’s ability to reach these services. Navigation services, where a person is tasked with helping connect patients to community resources, embedded within primary care may facilitate access and strengthen the continuity of care for patients. Objective: This study aims to describe the protocol to assess whether the implementation of the Access to Resources in the Community (ARC) navigation model (an innovative approach to navigation services) is feasible, including its potential to achieve its intended outcomes, and to assess the viability of the evaluation approach. Methods: The study consists of a single-arm, prospective, explanatory, mixed-methods, pre-post design feasibility study focusing on primary care practice settings with vulnerable populations. Participants include primary care providers and patients. Results: Enrollment is closed with 82 patients. Navigation services have ended for 69 patients. Conclusions: The study of an innovative complex intervention requires an adequate assessment of the feasibility of the intended approach during which the potential challenges of the planned intervention and need for its adaptation may be uncovered. Undertaking a feasibility study of the ARC navigation model from a conceptually clear and methodologically solid protocol will inform on the practicality and acceptability of the approach, demand for the services, ease of implementation, quality of integration of the new services within primary care, and practicality and potential for efficacy prior to initiating a randomized controlled trial.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Comprendre l’expérience des femmes âgées en matière de l’accessibilité aux services sociaux et de santé en contexte francophone minoritaire [mémoire de maîtrise, Université d'Ottawa] - Dubuc, Vanessa (Université d'Ottawa, 2019)
Au Canada, les francophones en contexte minoritaire demeurent contraints au niveau de l’accès aux services sociaux et de santé en français en raison de barrières linguistiques. De plus, les femmes âgées en contexte francophone minoritaire sont sujettes aux inégalités vécues par les femmes âgées de façon générale, mais subissent également de la discrimination liée à leur statut de minorité. La présente recherche s’intéresse à l’expérience des femmes âgées en contexte francophone minoritaire en matière d’accessibilité aux services sociaux et de santé. De manière plus précise, cette recherche a pour but : 1) d’identifier les facilitateurs et les défis rencontrés par ces femmes ; 2) de comprendre la manière dont ces facilitateurs et ces défis ont des effets sur les différentes sphères de leur vie ; 3) examiner l’effet des structures institutionnelles et organisationnelles quant à l’accessibilité aux services sociaux et de santé de celles-ci. Afin de recueillir nos données, des entrevues semi-structurées ont été effectuées auprès de quatre participantes. L’analyse thématique des données, suivant un cadre théorique féministe intersectionnel, permet de mettre en évidence les éléments suivants selon les expériences des participantes : 1) l’accès aux services sociaux et de santé en contexte francophone minoritaire ; 2) la question du genre ; et 3) les réalités structurelles. Concrètement, les résultats indiquent que les participantes ont de la difficulté à accéder à des services sociaux et de santé dans leur langue, mais que le fait de s’identifier comme une femme ne semble pas jouer un rôle déterminant dans leur accès aux services en français. À la lumière des résultats, des recommandations sont proposées afin de mieux répondre aux besoins des groupes en situation linguistique minoritaire. Mots clés : francophone minoritaire, femme âgée, accès aux services sociaux et de santé, féminisme intersectionnel

Leçons apprises sur la navigation des services de santé en français - Entité de planification des services de santé en français pour les régions de Waterloo, Hamilton, Niagara, Haldimand, Brant, Wellington (2019)
fs-ref-orig: Entité de planification des services de santé en français pour les régions de Waterloo, Wellington, Hamilton, Niagara, Haldimand, Brant. (2019). Leçons apprises sur la navigation des services de santé en français. fs-code-orig: Entité de planification des services de santé en français pour les régions de Waterloo, Wellington, Hamilton, Niagaram Haldminand, Brant-2019

Forum on Partnering for Innovative and Collaborative Long-Term Care Solutions for Francophones - Fondation Hélène Tremblay Lavoie Foundation; Reflet Salvéo (Fondation Hélène Tremblay Lavoie Foundation, 2019)
Access to French Language Services, more specifically to long term care beds and specialized dementia care units are not equitable and accessible across the Greater Toronto Area (GTA) and do not meet the specific needs of the Francophones in terms of location and language needs. Based on the goals of laying the foundation for action-oriented public / private / not-for-profit partnerships (social enterprise), better defining the needs of the Francophone community for specialized long-term care, and exploring innovative models that can be adapted to the different needs of the community, Fondation Hélène Tremblay Lavoie Foundation organized a one-day Forum to engage with different stakeholders on November 23, 2018 in Toronto. The one-day Forum ensured that key stakeholders, namely private/public sector, seniors, caregivers, health and social service providers, long-term care homes, retirement homes, financial institutions, developers and governments (LHINs, ministries, GTA municipalities), French Language Services Planning Entities (Reflet Salvéo and Entité 4) and post-secondary educational institutions such as Collège Boréal, Glendon, UOIT, York and Schulich and University of Toronto) came together to discuss on opportunities to - create an awareness of different programs and care models within the French community - facilitate access to and expansion of French health care services and programs for Francophone adults experiencing loss of autonomy - raise funds to support the improvement of long-term care and for an eventual capital project to support building the first bilingual long-term care facility dedicated to serving Francophone adults experiencing loss of autonomy within the GTA. This one-day engagement provided an opportunity for stakeholders the opportunity to make recommendations on moving forward. As such, 13 recommendations have developed for different stakeholders including the Francophone community.

Affichage de postes bilingues dans la région de Kingston. Un guide utile pour les employeurs des secteurs de la santé et des services sociaux et communautaires | Job posting resource for bilingual positions in the Kingston area. A useful guide for employers in the healthcare and social community services sectors - Réseau des services de santé en français de l'Est de l'Ontario (A useful guide for employers in the healthcare and social community services sectors, 2019)

Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)
fs-ref-orig: Savard, J., Savard, S., Van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019). Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/cahier_de_pratiques.html fs-code-orig: Savard-2019c